2013
DOI: 10.1371/journal.pone.0057968
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3ε Overexpression Contributes to Epithelial-Mesenchymal Transition of Hepatocellular Carcinoma

Abstract: Background14-3-3ε is implicated in regulating tumor progression, including hepatocellular carcinoma (HCC). Our earlier study indicated that elevated 14-3-3ε expression is significantly associated with higher risk of metastasis and lower survival rates of HCC patients. However, the molecular mechanisms of how 14-3-3ε regulates HCC tumor metastasis are still unclear.Methodology and Principal FindingsIn this study, we show that increased 14-3-3ε expression induces HCC cell migration and promotes epithelial-mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 42 publications
(52 reference statements)
6
74
1
Order By: Relevance
“…These properties are accompanied by a decrease in cell-cell adhesion and an increase in invasion and migration, all properties of invasive tumor cells. In contrast, two reports have suggested that other 14-3-3 isoforms, particularly 14-3-3⑀, can form a complex with the EMT transcription factor snail (80) and that 14-3-3⑀ is over-expressed in hepatocellular carcinoma and it contributes to the acquisition of the EMT phenotype (81). Importantly, 14-3-3 did not form a complex with snail (80), which is consistent with our observations that it preserves the epithelial phenotype.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These properties are accompanied by a decrease in cell-cell adhesion and an increase in invasion and migration, all properties of invasive tumor cells. In contrast, two reports have suggested that other 14-3-3 isoforms, particularly 14-3-3⑀, can form a complex with the EMT transcription factor snail (80) and that 14-3-3⑀ is over-expressed in hepatocellular carcinoma and it contributes to the acquisition of the EMT phenotype (81). Importantly, 14-3-3 did not form a complex with snail (80), which is consistent with our observations that it preserves the epithelial phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…The two 14-3-3 isoforms affect EMT progression by targeting different components in the EMT pathway, 14-3-3 by inducing c-Jun degradation and therefore preventing expression of slug (this report) and 14-3-3⑀ by forming a complex with the EMT transcription factor snail and stimulating snail-dependent transcription (80). These results are also consistent with the observation that 14-3-3 expression is low in multiple tumor types (16 -24), whereas 14-3-3⑀ expression is associated with the acquisition of EMT in hepatocellular carcinoma (81). Therefore, these are two distinct molecular mechanisms, and they reflect the diversity of mechanisms by which the 14-3-3 protein family regulates cellular pathways.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the outer surfaces of 14-3-3 isoforms are highly variable, and post-translational modifications (PTMs) 3 influence target/isoform specificity (for reviews, see Refs. [13][14][15][16][17][18][19]. Moreover, recent studies have indicated that 14-3-3 monomers are also functional (20); 14-3-3⑀-sv is a monomeric form of 14-3-3⑀ that lacks the exon encoding the N-terminal dimerization domain but remains functional and promotes cell survival similar to intact 14-3-3⑀ (21), and 14-3-3␥ S58N monomers interact with the scaffold protein kinase suppressor of Ras in the same manner as 14-3-3␥ dimers (22).…”
mentioning
confidence: 99%
“…Moreover, a histopathological study reported that in 114 hepatocellular carcinoma patients, elevated expression of 14-3-3ε was significantly associated with a high risk of metastasis and decreased survival rates [35]. Cellular experiments confirmed that increased 14-3-3ε expression induces hepatocellular carcinoma cell migration and promotes epithelial-mesenchymal transition (EMT) by inducing Zeb-1 and Snail expression [41]. To conclude, 14-3-3ε is a remarkable oncogene that participates in the development of several tumors and plays an important role in apoptosis and metastasis.…”
Section: Discussionmentioning
confidence: 94%